Conducting longitudinal, process-oriented research with conflict-affected youth: Solving the inevitable challenges. (21st November 2016) - Dubow, Eric F.; Aber, J. Lawrence; Betancourt, Theresa S.; Cummings, E. Mark; Huesmann, L. Rowell
Abstract: The reader might get the impression that the four projects described in this Special Section proceeded in a systematic and predictable way. Of course, those of us engaged in each research project encountered pitfalls and challenges along the way. A main goal of this Special Section is to provide pathways and encouragement for those who may be interested in advancing high-quality research on this topic. In this paper, we describe a set of practical and ethical challenges that we encountered in conducting our longitudinal, process-oriented, and translational research with conflict-affected youth, and we illustrate how problems can be solved with the goal of maintaining the internal and external validity of the research designs. We are hopeful that by describing the challenges of our work, and how we overcame them, which are seldom treated in this or any other literature on research on child development in high-risk contexts, we can offer a realistic and encouraging picture of conducting methodologically sound research in conflict-affected contexts.